Oxalic acid preharvest treatment improves colour and quality of seedless table grape ‘Magenta’ upregulating on-vine ABA metabolism and relative VvNCED1 gene expression and the antioxidant system in berries - García-Pastor, María E.; Giménez, María J.; Serna-Escolano, Vicente; Guillén, Fabián; Valero, Daniel; Serrano, María; García-Martínez, Santiago; Terry, Leon A.; Alamar, M. Carmen; Zapata, Pedro J. (Frontiers, 2021)
The effect of oxalic acid (OA) in determining poorly coloured table grape quality remains relatively unknown. Some red cultivars, such as seedless table grape ‘Magenta’ are characterised by a poor berry colour, an attribute highly demanded by the consumer. The aim of this research was to elucidate the effect of a preharvest OA treatment (5 mM) on berry colour and quality of table grape by investigating its role in berry development, on-vine ripening, and postharvest senescence. We found that OA significantly increased abscisic acid (ABA) and ABA glucose ester (ABA–GE) content in treated berries. This increase was mediated by changes in the ABA biosynthetic pathway, specifically by the upregulation of the 9-cis-epoxycarotenoid dioxygenase (VvNCED1) gene. The accumulation of ABA in treated berries resulted in colour improvement and a higher individual and total anthocyanins content at harvest compared with control; whereas at harvest, OA-treated table grapes showed a significantly lower glucose and fructose content and a higher content of tartaric, ascorbic, and succinic acids. Furthermore, antioxidant enzyme activity was increased during berry development in OA-treated berries. On the other hand, those berries treated with OA showed a delay in loss of firmness and colour during cold storage, as well as less susceptibility to postharvest decay incidence. This effect of OA delaying the senescence process was also related to enzymatic antioxidant system stimulation. For the first time, the role of OA on increasing quality, mainly colour, in table grapes was elucidated, highlighting that this treatment upregulated ABA metabolism, relative VvNCED1 gene expression and antioxidant system, delaying postharvest berry senescence.
Keywords: Vitis vinifera L.; anthocyanins; plant hormones; ripening; senescence